A Research On The Effect Of Istanbul Airport Technical Employees’ Motivation On Organizational Commitment - Ahmet Sabri Bostan; Seray Toksöz (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
Airport operators are called service operators. The most important factors which affect the quality of the services are the motivation of the employees and their commitment to organizations. Therefore, contemporary management approaches should investigate the factors that affect the motivation and organizational commitment of employees and find out the results.This study investigates the variables which influence the relationship between the motivation and organizational commitment of the technical electricity staff who work at Istanbul Airport. The method that was used in the research is the relational screening method which is one of the quantitative research methods. This screening method as “Motivation Scale” and “Organizational Commitment Scale” had been applied for the technical staff of the Istanbul Airport between October 1, 2019 and November 10, 2019. It is found out that there are significant differences based on gender, marital status, age, education level, working time in the corporate and position in terms of the motivation and commitment of the employees.